The Impact of Inquiry-Based Learning on Students' Critical Thinking and Learning Independence in Islamic Religious Education - Apriyani, Hikma; Jatmiko, Agus; Sunarto, Sunarto (STIT Ahlussunnah Bukittinggi, 2025)
This study aims to explore the implementation of the Inquiry-Based Learning (IBL) model in Islamic Religious Education at SMK Negeri 2 Bandar Lampung and evaluate its impact on students' critical thinking skills and learning independence. A qualitative approach with a case study design was employed, using in-depth interviews, classroom observations, and document analysis as data collection methods. The study found that the application of IBL significantly enhanced students’ critical thinking abilities and their capacity for independent learning. Teachers, in particular, reported increased student engagement in discussions and critical analysis of religious texts, such as tafsir and fiqh, through active exploration and collaborative learning. Students demonstrated a marked improvement in their analytical, evaluative, and synthetic thinking skills, as well as an increased independence in seeking learning resources and managing their study time. However, challenges related to time management and resource limitations were identified, which affected the full implementation of IBL. This study highlights the effectiveness of IBL in fostering critical thinking and independence in religious education and offers recommendations for its broader implementation in vocational schools. Future research should address the limitations of the current study by exploring the impact of IBL in diverse educational settings and incorporating more objective measures of critical thinking skills.